Upper body power as a determinant of classical cross-country ski performance - Alsobrook, N. G.; Heil, D. P. (European Journal of Applied Physiology, 2009)
The purpose of this study was to evaluate the relationship between short (=60 s) and long duration (4-12 min) measures of upper body power (UBP) and mass start classical cross-country ski performance. Several experienced skiers (eight men, five women) completed three separate tests of UBP on a double poling ergometer: two tests of highest average power output for 10 s (UBP10) and 60 s (UBP60), and an incremental test to exhaustion to measure peak oxygen uptake (VO2PEAK) and peak power output (UBPPEAK). Lastly, subjects competed in a 10-km classical cross-country ski race from which race speed (RS) was computed. RS correlated highly with UBP10 (r = 0.93; P < 0.05), UBP60 (r = 0.92; P < 0.05), and UBPPEAK (r = 0.94; P < 0.05); the correlation was lower but still significant for VO2PEAK (r = 0.88; P < 0.05). These findings suggest that both short and long duration measures of UBP are important determinants of mass start classical ski race performance.